Identification of HLA-DRPhe beta 47 as the susceptibility marker of hypersensitivity to beryllium in individuals lacking the berylliosis-associated supratypic marker HLA-DPGlu beta 69 - Amicosante, Massimo; Berretta, Floriana; Rossman, Milton; Butler, Richard H; Rogliani, Paola; Van den Berg-Loonen, Ella; Saltini, Cesare (Respiratory research, 2005)
Susceptibility to beryllium (Be)-hypersensitivity (BH) has been associated with HLA-DP alleles carrying a glutamate at position 69 of the HLA-DP beta -chain (HLA-DPGlu69) and with several HLA-DP, -DQ and -DR alleles and polymorphisms. However, no genetic associations have been found between BH affected subjects not carrying the HLA-DPGlu69 susceptibility marker. Methods In this report, we re-evaluated an already described patient populations after 7 years of follow-up including new 29 identified BH subjects. An overall population 36 berylliosis patients and 38 Be-sensitization without lung granulomas and 86 Be-exposed controls was analysed to assess the role of the individual HLA-class II polymorphisms associated with BH-susceptibility in HLA-DPGlu69 negative subjects by univariate and multivariate analysis. Results As previously observed in this population the HLA-DPGlu69 markers was present in higher frequency in berylliosis patients (31 out of 36, 86%) than in Be-sensitized (21 out of 38, 55%, p = 0.008 vs berylliosis) and 41 out of 86 (48%, p < 0.0001 vs berylliosis, p = 0.55 vs Be-sensitized) Be-exposed controls. However, 22 subjects presenting BH did not carry the HLA-DPGlu69 marker. We thus evaluated the contribution of all the HLA-DR, -DP and -DQ polymorphisms in determining BH susceptibility in this subgroup of HLA-Glu69 subjects. In HLA-DPGlu69-negatives a significant association with BH was found for the HLA-DQLeu26, for the HLA-DRB1 locus residues Ser13, Tyr26, His32, Asn37, Phe47 and Arg74 and for the HLA-DRB3 locus clusterized residues Arg11, Tyr26, Asp28, Leu38, Ser60 and Arg74. HLA-DRPhe47 (OR 2.956, p < 0.05) resulting independently associated with BH. Further, Be- stimulated T-cell proliferation in the HLA-DPGlu69-negative subjects (all carrying HLA-DRPhe47) was inhibited by the anti-HLA-DR antibody (range 70-92% inhibition) significantly more than by the anti-HLA-DP antibody (range: 6-29%; p < 0.02 compared to anti-HLA-DR) while it was not affected by the anti-HLA-DQ antibody. Conclusion We conclude that HLA-DPGlu69 is the primary marker of Be- hypersensitivity and HLA-DRPhe47 is associated with BH in Glu69-negative subjects, likely playing a role in Be-presentation and sensitization.